Global well-posedness, asymptotic behavior and blow-up of solutions for a class of degenerate parabolic equations. (July 2020) - Liu, Yang; Yu, Tao; Li, Wenke
Abstract: The initial–boundary value problem for a class of degenerate parabolic equations is studied. Some new results on global existence of solutions are established by introducing a family of potential wells. In addition, asymptotic behavior and finite time blow-up of solutions are obtained in the case of subcritical initial energy and critical initial energy, respectively.